Food, energy, and society - Pimentel, David , 1925-; Pimentel, Marcia H. (CRC Press, 2008)
Presents an analysis on the interdependency of food, energy, water, land, and biological resources. This book includes material on livestock production and energy use, the impacts of pesticides on the environment, and the conservation of biodiversity in agricultural, forestry, and marine systems.